2016
DOI: 10.1007/s10900-016-0288-1
|View full text |Cite
|
Sign up to set email alerts
|

Community BMI Surveillance Using an Existing Immunization Registry in San Diego, California

Abstract: This study examines the demographic representativeness of the County of San Diego Body Mass Index (BMI) Surveillance System to determine if the BMI estimates being obtained from this convenience sample of individuals who visited their healthcare provider for outpatient services can be generalized to the general population of San Diego. Height and weight were transmitted from electronic health records systems to the San Diego Immunization Registry (SDIR). Age, gender, and race/ethnicity of this sample are compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Finally, this study has demonstrated the potential for the SOMI platform to determine whether spatial, environmental, sociodemographic and health-related factors differ among those with and without a known genetic contribution to infant mortality. As with previous population studies of San Diego County, many of the results will have generalizable implications 100 103 .…”
Section: Discussionmentioning
confidence: 56%
“…Finally, this study has demonstrated the potential for the SOMI platform to determine whether spatial, environmental, sociodemographic and health-related factors differ among those with and without a known genetic contribution to infant mortality. As with previous population studies of San Diego County, many of the results will have generalizable implications 100 103 .…”
Section: Discussionmentioning
confidence: 56%